IDENTIFIKASI NEMATODA GASTROINTESTINAL PADA KATAK Fejervarya Cancrivora DAN Limnonectes Macrodon DI WILAYAH KABUPATEN BOGOR, JAWA BARAT (Gastrointestinal Nematode Identification of frogs Fejervarya cancrivora and Limnonectes macrodon in Bogor Residence) - Erna Suzanna; Fadjar Satrija; Mirza Dikari Kusrini; Dwi Fania (Media Konservasi, 2006)
A research was conducted to identify and to descript nematode worm genera as parasite from gastrointestinal tract of local consumption frogs. Fifty five adult Fejervarya cancrivora and seventy Limnonectes macrodon were collected from three subdistricts in Bogor Residence; Caringin, Cibatok, and Cimanggis. The research was also carried out to quantify prevalence nematode that infest both of frogs and to observe relationship between prevalence level and resource area also spesies of its. Nematode generas which found in F. cancrivora were identified as Amplicaecum, Camallanus, Aplectana, Cosmocerca, Cosmocercella,and Spinicauda. The same generas infested L. macrodon for exception Camallanus. Fejervarya cancrivora nematode prevalence level was higher than L. macrodon in all subdistricts. Its prevalence level weren’t influenced by resource area. But, there was significant correlation between prevalence level and species of frogs (α=0,01 and α=0,05). The differences of gastrointestinal nematode infestation are related to differences in habitat and food type of frogs also life cycle of nematodes.Keywords: Fejervarya cancrivora, Limnonectes macrodon, Amplicaecum, Camallanus, Aplectana, Cosmocerca, Cosmocercella,and Spinicauda